Identifying pastoral care in contemporary Methodism - Burfield, David R. (1995)
This study is concerned with the nature of pastoral care and its practice in contemporary British Methodism. Both aspects are explored by means of postal surveys of Methodist ministers, local preachers and other lay members, as well as case study interviews with circuit ministers. These explorations take place in the context of a brief historical overview of the roots of Methodism and a characterisation of the theological viewpoints and spirituality of respondents, which are correlated with the findings of an earlier Anglican study. At the same time a detailed portrait is painted of the biography and ministry of both ministers and local preachers as an aid to understanding their contribution to pastoral care. The nature of pastoral care is discussed and a working definition proposed which emphasises the importance of nurture rather than crisis-oriented care. The perceptions of ministers and local preachers regarding their understanding of the nature of pastoral care are examined, and the influence of theological viewpoint, gender and age is explored. Pastoral practice within Methodism is evaluated and some difficulties and areas of weakness are pin-pointed. Comparison of the perceptions and practice of pastoral care reveals that whereas ministers have a balanced view of pastoral care, frequently such care tends to be crisis-oriented and ministers driven rather than in control of the task: essentially reactive rather than pro-active. A weakness of pastoral care is that it tends to be centred on the full-time professional rather than involving the whole community of faith. It is argued that the divisions between lay and ordained members of the church need to be removed in order to permit effective pastoral care. A working model of pastoral care is proposed, within a Methodist context, which emphasises the functional nature of full-time personnel and the importance of local leadership.